An analysis of the content-neutrality approach in European audiovisual market regulation. The case of potential harmful content for minors - MTeresa Arcos; Claudio Feijóo (International Telecommunications Society (ITS), 2022)
Boundaries set between legacy audiovisual and digital content services are blurring nowadays. However, the legal framework applicable to those services is still rather different to such an extent it is recognized as divergent, particularly regarding the liability regime of the service providers. Among the examples of these distinct regimes, the protection for minors with access to potentially harmful content regarding their moral and mental growth is used in the paper to analyse the lack of coherence in the legal treatment of audiovisual content, in the EUin particular. From the analysis, the paper concludes that the Digital Services Act, as the latest step in theevolution of the legal framework for the digital services in the EU still seems unable to restore the required level of coherence and level the playing field for audiovisual content. and, therefore, lacks content-neutrality from the perspective of technology used for the distribution of content. Therefore, the paper foresees that more legislative initiatives will be needed to avoid the negative effects of the difficulties of existing audiovisual legislative framework enforcement and perceived lack of trust in law.
Keywords: 330; digital services regulation; audiovisual regulation; neutrality; content-neutrality; technology-neutrality European audiovisual market; Digital Single Market; liability intermediaries; AVSMD; DSA; harmful content; minors